2018
DOI: 10.1038/s41395-018-0025-8
|View full text |Cite
|
Sign up to set email alerts
|

Rapid on-site evaluation during endoscopic ultrasoundguided fine-needle aspiration of lymph nodes does not increase diagnostic yield: A randomized, multicenter trial

Abstract: Diagnostic yield and accuracy of EUS-FNA of mediastinal and abdominal lymph nodes with and without ROSE are comparable. Time needed to review slides was shorter and post-procedural pain was less often reported in the ROSE+ group. Based on the primary outcome, the implementation of ROSE during EUS-FNA of mediastinal and abdominal lymph nodes cannot be advised. (Dutch Trial Register: NTR4876).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 36 publications
1
28
0
Order By: Relevance
“…29 Severe adverse events are very rare. 6,23,30 In our study, similar to several studies that compared FNA and FNB, no adverse events were reported. 30,31 Currently, this is the largest study to exclusively evaluate EUS-guided LN sampling.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…29 Severe adverse events are very rare. 6,23,30 In our study, similar to several studies that compared FNA and FNB, no adverse events were reported. 30,31 Currently, this is the largest study to exclusively evaluate EUS-guided LN sampling.…”
Section: Discussionsupporting
confidence: 86%
“…26,27 Specifically for LNs, a multicenter randomized controlled trial showed that the diagnostic yield and accuracy of EUS-FNA in mediastinal and abdominal LNs with or without ROSE were comparable. 23 However, the time required to review slides was shorter and post-procedural pain was less often reported in the ROSE group. In our study, ROSE was selectively utilized, usually in cases that were more challenging or had failed prior sampling.…”
Section: Discussionmentioning
confidence: 96%
“…A meta-analysis and systematic review by Kong et al showed that the use of ROSE did not improve the diagnostic yield and accuracy, nor did it improve the pooled sensitivity and specificity for EUS-FNA of pancreatic masses [22]. Similarly, a Dutch group studied the impact of ROSE during EUS-FNA of mediastinal and abdominal lymph nodes; the multicenter, randomized trial showed that EUS-FNA with and without ROSE were comparable in terms of diagnostic yield and accuracy [23]. When EUS-FNA is performed by a skilled endosonographer in a center with a high diagnostic rate, ROSE may offer no benefit to the standard approach [24][25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…However, the widespread implementation of this form of evaluation is hampered by a number of factors [1-4]. First, randomized trials and meta-analyses have clearly demonstrated that ROSE does not increase the diagnostic yield or the specimen adequacy of conventional transbronchial needle aspiration (c-TBNA) or endosonography-derived samples from lymphadenopathy [5-11]. As a consequence, according to international guidelines, there is insufficient evidence to recommend the implementation of ROSE for every endosonography procedure [12, 13].…”
Section: Introductionmentioning
confidence: 99%